2017
DOI: 10.1021/acs.joc.7b01964
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Desymmetrization of Prochiral Cyclopentenediones via Cycloaddition Reaction with N-Phenacylbenzothiazolium Bromides

Abstract: A metal-free highly diastereoselctive [3 + 2] cycloaddition reaction has been developed between N-phenacylbenzothiazolium bromides and prochiral cyclopentene-1,3-diones. The active 1,3 dipole benzothiazolium N-phenacylide was generated in situ with the treatment of DIPEA, and the corresponding cycloaddition products were obtained in excellent yields under mild reaction conditions. The scope of the reaction is quite broad, tolerating a variety of aryl and heteroaromatic groups. A catalytic asymmetric approach w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Based on our experimental results and previous related reports [ 30 , 31 , 32 , 33 ], a plausible catalytic mechanism involving a stepwise reaction process was assumed to explain the stereoselectivity of the 1,3-dipolar cycloaddition of N -2,2,2-trifluoroethylisatin ketimines and cyclopentene-1,3-diones. As depicted in Scheme 5 , the N -2,2,2-trifluoroethylisatin ketimine 1 is deprotonated under a basic condition to yield the 2-azaallyl anion intermediate I .…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Based on our experimental results and previous related reports [ 30 , 31 , 32 , 33 ], a plausible catalytic mechanism involving a stepwise reaction process was assumed to explain the stereoselectivity of the 1,3-dipolar cycloaddition of N -2,2,2-trifluoroethylisatin ketimines and cyclopentene-1,3-diones. As depicted in Scheme 5 , the N -2,2,2-trifluoroethylisatin ketimine 1 is deprotonated under a basic condition to yield the 2-azaallyl anion intermediate I .…”
Section: Resultsmentioning
confidence: 53%
“…However, an extensive ature search revealed that the related 1,3-dipolar cycloaddition reaction with cyclo tene-1,3-diones as electrophilic dipolarophiles has been little explored. In 2015, the W and Singh groups independently reported Ag(I)-catalyzed desymmetrization of pro ral cyclopentenediones via formal 1,3-dipolar cycloaddition with azomethine-ylid the synthesis of highly functionalized 5,5-fused bicyclic pyrrolidine derivatives [30 Later, using DIPEA as the base, the diastereoselective 1,3-dipolar cycloaddition reac of cyclopentene-1,3-diones and N-phenacylbenzothiazolium bromides for the synth of tetracyclic products bearing five stereogenic centers was described by the group of [32]. In 2018, an efficient kinetic resolution of readily available racemic cyclo tene-1,3-diones was developed via Ag(I)-catalyzed asymmetric 1,3-dipolar cycloadd of azomethine ylides [33].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, benzothiazolium salts serving as heteroaromatic N-ylide precursors are extremely valuable for the simple and efficient synthesis of N,S-polyheterocyclic derivatives which are frequently found in natural products and pharmaceuticals [45][46][47][48]. However, a literature search revealed that, although many types of electron-deficient olefins acting as 2π-component have been successfully applied in [3 + 2] cycloaddition with various three-atom 4π-component partners [11][12][13][14][15][16]49,50], the related [3 + 2] cycloaddition reaction concerning the heteroaromatic N-ylides, in situ generated from benzothiazolium salts, with diverse electron-deficient olefins is very limited [51][52][53][54][55][56]. In this context, given the importance of N,S-polyheterocyclic scaffolds in medicinal and natural product chemistry and the great potential of the benzothiazolium salts for cycloaddition, expanding the application of benzothiazolium salts in the reaction with different type of electron-deficient olefins for the [3 + 2] cycloaddition to access structurally diverse polyheterocyclic compounds is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, Pan et al disclosed a solitary instance of an asymmetric variant of [3 + 2] cycloaddition of benzothiazolium salt, utilizing hydroquininederived thiourea as a chiral catalyst to afford a product exhibiting moderate enantioselectivity (43% ee, Scheme 1a). 18 Subsequently, Feng et al reported the synthesis of dihydropyrrolo-thiazoles and [1,4]thiazine derivatives via asymmetric [3 + 2] cycloaddition and rearrangement of benzothiazolium salt with variety of dipolarophiles employing chiral N,N′-dioxide-metal salts (Mg and Ni salts) (Scheme 1b). 19 Vicario et al reported the use of chiral proline-derived organocatalyst for the [3 + 2] cycloaddition of azomethine ylide with dipolarophile to construct polysubstituted pyrrolidines (Scheme 1c).…”
mentioning
confidence: 99%
“…The enantioselective transformations of benzothiazolium azomethine ylides to the synthesis of multiple stereogenic centers containing pyrrolo-thiazine and its derivatives are a daunting challenge, and only a few reports have been documented in the scientific literature. In 2017, Pan et al disclosed a solitary instance of an asymmetric variant of [3 + 2] cycloaddition of benzothiazolium salt, utilizing hydroquinine-derived thiourea as a chiral catalyst to afford a product exhibiting moderate enantioselectivity (43% ee, Scheme a) . Subsequently, Feng et al reported the synthesis of dihydropyrrolo-thiazoles and [1,4]­thiazine derivatives via asymmetric [3 + 2] cycloaddition and rearrangement of benzothiazolium salt with variety of dipolarophiles employing chiral N,N′ -dioxide-metal salts (Mg and Ni salts) (Scheme b) .…”
mentioning
confidence: 99%